Integrating Debate in Speaking Learning Through Project Based Learning: Case Study at a Senior High School in Bekasi - Aulia Humairo Buhaeri; Sumarta Sumarta; Iwan Ridwan (FKIP - Universitas Riau, 2026)
Speaking activities in English classrooms often remain teacher-centered and lack opportunities for students to develop critical thinking. This study aims to analyze how debate activities facilitate teachers in implementing Project-Based Learning (PBL) in speaking instruction and to identify the challenges encountered during its application. Using a qualitative method with a case study design, the research was conducted at a senior high school in Bekasi. Data were collected through classroom observations and interviews with an English teacher and analyzed using thematic analysis. The results revealed that integrating debate into PBL effectively enhanced students’ speaking skills, particularly in fluency, pronunciation, vocabulary, and confidence. The teacher’s role shifted from instructor to facilitator, creating a more active and student-centered learning environment. Despite challenges such as limited time, varying student abilities, and inadequate school facilities, the debate-based PBL approach proved to promote communication, collaboration, critical thinking, and creativity. In conclusion, debate integration within PBL serves as an effective model to improve both linguistic competence and 21st-century learning skills.